Shaped adsorbent and water purification filter cartridge

CN122995903APending Publication Date: 2026-10-27LIXIL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480090081.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

用于解决技术问题的技术方案

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995903A_ABST
    Figure CN122995903A_ABST
Patent Text Reader

Abstract

The present invention provides a molded adsorbent capable of ensuring shape retention. A molded adsorbent (1) contains activated carbon (3) and a fibrous binder (7), wherein the fibrous binder (7) is a mixture of a first fibrous binder (7A) and a second fibrous binder (7B), the second fibrous binder (7B) has a different particle size distribution from the first fibrous binder (7A), in the case where the first fibrous binder (7A) is measured using a laser diffraction / scattering type particle size distribution measuring device, a measured value obtained as a center particle diameter D50 is 80 μm or more and 300 μm or less, and in the case where the second fibrous binder (7B) is measured using a laser diffraction / scattering type particle size distribution measuring device, a measured value obtained as a center particle diameter D50 is 14 μm or more and 60 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to shaped adsorbents and water purification filter cartridges. Background Technology

[0002] Patent Document 1 discloses a water treatment filter. The water treatment filter in Patent Document 1 comprises a cylindrical filter including granular activated carbon and fibrillated fibrous binder. As the fibrous binder, an example is described using only "fibrillated acrylic pulp Bi-PUL / F" manufactured by Japan Exlan Co., Ltd. Existing technical documents Patent documents

[0003] Patent Document 1: WO2014 / 061740 Summary of the Invention The technical problem that the invention aims to solve

[0004] Conventional molded adsorbents using fibrous binders tend to crack during drying. The purpose of this disclosure is to provide a molded adsorbent that suppresses cracking during drying and ensures shape retention. Technical solutions for solving technical problems

[0005] The shaped adsorbent disclosed herein contains activated carbon and a fibrous binder, wherein the fibrous binder is a mixture of a first fibrous binder and a second fibrous binder, the second fibrous binder having a different particle size distribution than the first fibrous binder. When the first fibrous binder is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 80 μm or more and 300 μm or less. When the second fibrous binder is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 14 μm or more and 60 μm or less. Attached Figure Description

[0006] Figure 1 This is an illustrative diagram schematically representing the structure of a shaped adsorbent. Figure 2 This is a front view of an example of a water filter cartridge with a shaped adsorbent. Figure 3 yes Figure 2 A cross-sectional view of a water purification filter cartridge. Figure 4 It is a frequency distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size and the vertical axis set to frequency. Figure 5It is a cumulative distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size and the vertical axis set to cumulative volume. Detailed Implementation

[0007] First, embodiments of this disclosure are listed for description. Regarding the following multiple embodiments, any combination of embodiments without contradiction is also included in the specific embodiments of this invention. [1] The shaped adsorbent disclosed herein contains activated carbon and a fibrous binder, wherein the fibrous binder is a mixture of a first fibrous binder and a second fibrous binder, the second fibrous binder having a different particle size distribution than the first fibrous binder. When the first fibrous adhesive was measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 was 80 μm or more and 300 μm or less. When the second fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 14 μm or more and 60 μm or less. [2] According to the shaped adsorbent described in [1] above, the content of the activated carbon with a particle size of 10 μm or less is 12% by volume or less. [3] According to the shaped adsorbent described in [1] or [2] above, wherein, when the fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the content of the fibrous adhesive with a particle size of 23.99 μm or less is 11% by volume or more and 30% by volume or less. [4] The water purification filter element disclosed herein comprises the shaped adsorbent described in any one of [1] to [3] above.

[0008] The embodiments of this disclosure will be described with reference to the accompanying drawings. It should be noted that in this specification, the terms "above" and "below" are used to describe numerical ranges, and unless otherwise specified, they include both the lower limit and the upper limit. For example, the statement "10 or more and 20 or less" includes both "10" as the lower limit and "20" as the upper limit. Furthermore, in this specification, the upper and lower limits of each numerical range can be arbitrarily combined.

[0009] like Figure 1 As shown, the shaped adsorbent 1 of this embodiment contains activated carbon 3 and fibrous binder 7. The shaped adsorbent 1 may also contain one or more lead removal materials 5 selected from the group consisting of zeolite, titanium silicate, sodium titanate, aluminosilicate, and titanium oxide. Figure 1 This is an illustrative diagram schematically representing the structure of the formed adsorbent 1. The size, shape, and amount of each component are not limited thereto. Figure 1 The arrow indicates the direction of water flow purified by the shaped adsorbent 1.

[0010] Activated carbon 3 can be obtained from any starting material. Specific examples of activated carbon 3 include activated carbon obtained by carbonizing and activating one or more of the following materials at high temperature: coconut shell, rice husk, coal, and phenolic resin. The form of activated carbon 3 is not particularly limited. Activated carbon 3 may be, for example, in granular form.

[0011] The activated carbon 3 is not particularly limited as long as it does not affect the desired effect. From the viewpoint of ensuring the initial flow rate, the center particle size D50 of the activated carbon 3 is preferably 16 μm or more, more preferably 19 μm or more, further preferably 20 μm or more, and may also be 25 μm or more. The center particle size D50 of the activated carbon 3 is generally 160 μm or less, and may be 90 μm or less, 60 μm or less, or 40 μm or less. From the viewpoint of improving chloroform removal capacity, it is preferably 27 μm or less, more preferably 26 μm or less, and further preferably 25 μm or less. From these viewpoints, the center particle size D50 of the activated carbon 3 is preferably 16 μm or more and 27 μm or less, more preferably 19 μm or more and 26 μm or less, and further preferably 20 μm or more and 25 μm or less.

[0012] From the viewpoint of improving chloroform removal capacity, the content of activated carbon 3 with a particle size of 10 μm or less is preferably 1% by volume or more, more preferably 3% by volume or more, even more preferably 5% by volume or more, and can be 7% by volume or more, or 8% by volume or more. From the viewpoint of ensuring initial flow rate, the content of activated carbon 3 with a particle size of 10 μm or less is preferably 15% by volume or less, more preferably 10% by volume or less, and even more preferably 8% by volume or less. From these viewpoints, the content of activated carbon 3 with a particle size of 10 μm or less is preferably 1% by volume or more and 15% by volume or less, more preferably 3% by volume or more and 10% by volume or less, and even more preferably 5% by volume or more and 8% by volume or less. The content of activated carbon 3 with a particle size of 10 μm or less refers to the volume percentage of activated carbon 3 with a particle size of 10 μm or less contained in 100% by volume of the total amount of activated carbon 3. The particle size of activated carbon 3 with a particle size of 10 μm or less is greater than 0 μm.

[0013] The central particle size D50 of activated carbon 3 and the content of activated carbon 3 with a particle size of less than 10 μm can be determined by a laser diffraction / scattering particle size distribution measuring device.

[0014] The central particle size D50 and particle size distribution of activated carbon 3 can be controlled, for example, by appropriately selecting the particle size of the activated carbon used as raw material. When activated carbon 3 is a mixture of activated carbons with different particle sizes, the mixing amount of activated carbons of each particle size can be adjusted for control.

[0015] The content of activated carbon 3 is not particularly limited. From the viewpoint of chloroform removal performance, when the formed adsorbent 1 is set to 100% by mass, the content of activated carbon 3 is 64% by mass or more and 96% by mass or less, more preferably 75% by mass or more and 94% by mass or less, and even more preferably 80% by mass or more and 92% by mass or less.

[0016] The fibrous adhesive 7 can be a synthetic fiber or a natural fiber. For example, the fibrous adhesive 7 is selected from one or more fibers chosen from the group consisting of acrylic fibers, polyethylene fibers, polypropylene fibers, polyacrylonitrile fibers, cellulose fibers, polyamide fibers, and aromatic polyamide fibers. Acrylic fibers are preferred. From the viewpoint of maintaining the shape of the formed adsorbent 1, it is preferable that the fibrous adhesive 7 is fibrillated.

[0017] Conventional shaped adsorbents use fibrous binders to maintain their shape. However, when the activated carbon particle size is small, the same amount of fibrous binder sometimes fails to completely maintain the shape of the activated carbon, resulting in cracking. If the amount of fibrous binder is increased to maintain shape, the density and packing weight of the activated carbon decrease, and the removal performance may also decline. The inventors of this application have conducted repeated and in-depth research and developed a new technology that balances the packing weight and shape retention of activated carbon by mixing fine-particle fibrous binder into conventional fibrous binders.

[0018] It should be noted that, as is known in the present disclosure, the fibrous adhesives 7, 7A, and 7B can also be appropriately evaluated through particle size distribution measurement, just like the particle size distribution of activated carbon 3. Therefore, the fibrous adhesives 7, 7A, and 7B of the present disclosure are defined by the measured values ​​obtained using a laser diffraction / scattering particle size distribution measuring device.

[0019] From the viewpoint of ensuring the shape retention of the formed adsorbent 1 and the filling amount of activated carbon 3, the fibrous binder 7 is preferably a mixture of a first fibrous binder 7A and a second fibrous binder 7B having a different particle size distribution than the first fibrous binder 7A. The first fibrous binder 7A and the second fibrous binder 7B can be of the same type of fiber or different types of fiber, provided they have different particle size distributions. The first fibrous binder 7A and the second fibrous binder 7B are preferably of the same type of fiber, and more preferably both are acrylic fibers. Such a second fibrous binder 7B can be obtained, for example, by subjecting the first fibrous binder 7A to a particle size reduction process. The particle size reduction process includes, for example, pulverization or grading.

[0020] When the first fibrous adhesive 7A is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 80 μm or more and 300 μm or less, preferably 90 μm or more and 200 μm or less, and more preferably 100 μm or more and 160 μm or less. When the second fibrous adhesive 7B is measured using the laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 14 μm or more and 60 μm or less, preferably 18 μm or more and 40 μm or less, and more preferably 20 μm or more and 30 μm or less.

[0021] When measuring the fibrous adhesive 7 using a laser diffraction / scattering particle size distribution measuring device, the measured value obtained as the central particle size D50 is preferably 50 μm or more and 140 μm or less, more preferably 70 μm or more and 130 μm or less, and even more preferably 90 μm or more and 120 μm or less.

[0022] From the viewpoint of improving the shape retention of the formed adsorbent 1, when the fibrous adhesive 7 is measured using a laser diffraction / scattering particle size distribution measuring device, the content of the fibrous adhesive 7 with a measured particle size of 23.99 μm or less is preferably 11 vol% or more, more preferably 14 vol% or more, and even more preferably 16 vol% or more. From the viewpoint of ensuring the initial flow rate, the content of the fibrous adhesive 7 with a measured particle size of 23.99 μm or less is preferably 30 vol% or less, more preferably 25 vol% or less, and even more preferably 20 vol% or less. From these viewpoints, the content of the fibrous adhesive 7 with a measured particle size of 23.99 μm or less is preferably 11 vol% or more and 30 vol% or less, more preferably 14 vol% or more and 25 vol% or less, and even more preferably 16 vol% or more and 20 vol% or less. The content of fibrous adhesive 7 with a particle size of 23.99 μm or less refers to the volume percentage of fibrous adhesive 7 with a particle size of 23.99 μm or less contained in 100% by volume of the total amount of fibrous adhesive 7. Fibrous adhesive 7 with a particle size of 23.99 μm or less has a particle size greater than 0 μm.

[0023] The ratio (mass ratio) of the first fibrous adhesive 7A to the second fibrous adhesive 7B is not particularly limited. The mass ratio of the first fibrous adhesive 7A to the second fibrous adhesive 7B is preferably 5:5 to 9.9:0.1, more preferably 6:4 to 9.5:0.5, and even more preferably 7:3 to 9:1.

[0024] The content of the fibrous adhesive 7 is not particularly limited. When the shaped adsorbent 1 is set to 100% by mass, the content of the fibrous adhesive 7 is preferably 4% by mass or more and 12% by mass or less, more preferably 5% by mass or more and 11% by mass or less, and even more preferably 6% by mass or more and 10% by mass or less.

[0025] The lead removal material 5 is not particularly limited, provided it does not affect the desired effect. The lead removal material 5 may be, for example, one or more selected from the group consisting of zeolite, titanium silicate, sodium titanate, aluminosilicate, and titanium oxide, with zeolite being preferred. The form of the lead removal material 5 is not particularly limited. The lead removal material 5 may be, for example, in particulate form.

[0026] From the viewpoint of ensuring water flow by matching the particle size of the second fibrous binder 7B, the center particle size D50 of the lead removal material 5 is preferably 25 μm or more and 40 μm or less, more preferably 28 μm or more and 37 μm or less, and even more preferably 30 μm or more and 35 μm or less. The center particle size D50 of the lead removal material 5 can be measured using a laser diffraction / scattering particle size distribution measuring device.

[0027] The content of lead-removing material 5 is not particularly limited. When the shaped adsorbent 1 is set to 100% by mass, the content of lead-removing material 5 is preferably 2.5% by mass or more and 32% by mass or less, more preferably 3.0% by mass or more and 20% by mass or less, and even more preferably 4.5% by mass or more and 12% by mass or less.

[0028] The pressure loss of the shaped adsorbent 1 is preferably 0.07 MPa or more and 0.15 MPa or less. Such a pressure loss makes the shaped adsorbent 1 practical. Pressure loss refers to the pressure loss when water flows from the outer circumference to the inner circumference at a flow rate of 1.5 L / min in a cartridge filter with an outer diameter of 24.4 mm, an inner diameter of 8.1 mm, and a length of 90.0 mm and a filtration volume of 37.4 mL.

[0029] The density of the formed adsorbent 1 is preferably 0.28 g / cm³. 3 Above and 0.45g / cm 3 The preferred value is 0.35 g / cm³. 3 Above and 0.43 g / cm 3 The following is a further preferred value: 0.38 g / cm³ 3 Above and 0.41 g / cm 3 The density of the shaped adsorbent 1 is defined based on its mass (g) and volume (cm³). 3 The apparent density is calculated from this.

[0030] The water purification filter element 11 of this embodiment includes a shaped adsorbent 1. The shape and structure of the water purification filter element 11 are not particularly limited. Figure 2 and Figure 3 As shown, an example water filter cartridge 11 is cylindrical. This water filter cartridge 11 includes a core 12, a shaped absorbent 1, a non-woven fabric 14, and sealing caps 15 and 16. The core 12 is cylindrical and disposed at the innermost part of the water filter cartridge 11. The core 12 has fine pores that allow water to pass through from the outside to the inside, and a flow path 20 is formed inside. The core 12 can be made of any material. For example, the material of the core 12 is porous ceramic, porous metal filter, or rigid non-woven fabric.

[0031] In one example, the shaped absorbent 1 is cylindrical and disposed on the outer peripheral surface of the core 12. Nonwoven fabric 14 is disposed on the outer peripheral surface of the shaped absorbent 1. The nonwoven fabric 14 may be, for example, a nonwoven fabric specified in JIS L0222. There are no particular limitations on the type of fiber used as the raw material for the nonwoven fabric 14.

[0032] The sealing cap 15 blocks one side of the flow path 20 by covering one end of the shaped adsorbent 1. The sealing cap 16 covers the other end of the shaped adsorbent 1. An outlet 60 is formed in the sealing cap 16 for the discharge of water flowing in the flow path 20.

[0033] There is no particular limitation on the manufacturing method of the water purification filter element 11. The manufacturing method of the water purification filter element 11 may include a mixing process, a suction forming process, a drying process, a surface grinding process, a non-woven fabric winding process, and a sealing process.

[0034] The mixing process involves mixing particulate matter containing at least activated carbon 3, fibrous binder 7, and water to obtain a slurry. The suction forming process shapes the adsorbent 1. For example, the suction forming process includes: sealing one end of the flow path 20 of the core 12; connecting one end of the flow path 20 of the core 12 to a suction pump via a hose; immersing the core 12 connected to the suction pump in the aforementioned slurry accumulated in a container; and operating the suction pump; water in the slurry permeates through the core 12, and the mixture of particulate matter and binder remains and gradually accumulates on the surface of the core 12. Water in the slurry suctioned by the suction pump is discharged through a drainage path. By operating the suction pump, the shaped adsorbent 1 is formed to a predetermined thickness.

[0035] The drying process dries the shaped adsorbent 1 formed in the suction forming process. The surface grinding process grinds the outer peripheral surface of the shaped adsorbent 1. The nonwoven fabric winding process winds nonwoven fabric 14 around the outer peripheral surface of the shaped adsorbent 1 after grinding in the surface grinding process. The sealing process installs a sealing cap 15 on one end of the shaped adsorbent 1 with nonwoven fabric 14 wound on it, and a sealing cap 16 on the other end.

[0036] As explained above, the shaped adsorbent 1 of this embodiment contains activated carbon 3 and a fibrous binder 7. The fibrous binder 7 is a mixture of a first fibrous binder 7A and a second fibrous binder 7B having a different particle size distribution than the first fibrous binder 7A. When the first fibrous binder 7A is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 80 μm or more and 300 μm or less. When the second fibrous binder 7B is measured using the same device, the measured value as the central particle size D50 is 14 μm or more and 60 μm or less. The shaped adsorbent 1 of this embodiment, for example, improves the shape retention compared to a shaped adsorbent containing only the first fibrous binder 7A as the fibrous binder. By combining activated carbon 3 and fibrous binder 7, the shaped adsorbent 1 can appropriately ensure the required chloroform removal capacity and initial flow rate as a shaped adsorbent 1. Example

[0037] Examples 4, 5, 6, 10, and 11 are examples, while examples 1, 2, 3, 7, 8, and 9 are comparative examples. In Table 1, "*" indicates a comparative example.

[0038] The formed adsorbents for each experimental example were prepared as described below. First, the experimenter prepared a slurry with a total amount of activated carbon, lead-removing material, and fibrous binder of 100% by mass, according to the following mixing ratio. The amount of fibrous binder was the total amount of the first fibrous binder and the second fibrous binder. <Slurry mixing ratio> Activated carbon: 80% by mass or more and 92% by mass or less; Lead-free materials: 4.5% by mass or more and 12% by mass or less; Fibrous adhesives: 6% by mass or more and 10% by mass or less.

[0039] Details of each ingredient are shown below. - Activated carbon: Particle-shaped activated carbon having the particle size distribution described in Table 1; - Lead removal materials: zeolite BASF Japan ATS TM MEDIA NSF / ANSI61 D50=29μm; - Fibrous binder: This is a mixture formed by mixing the first fibrous binder and the second fibrous binder at the mass ratios shown in Table 1, and the particle size distribution of the mixture is shown in Table 1 when measured using a laser diffraction / scattering particle size distribution measuring device. It should be noted that the values ​​recorded in the "Mass Ratio" column of Table 1 are the content (mass%) of each component when the formed adsorbent is set to 100% by mass. First fibrous adhesive: Toyobo Co., Ltd., and Exlan Kogyo Co., Ltd. of Japan, Bi-PUL 50 TWF (acrylonitrile fibrillated fiber). The measured D50 value is 131.5 μm; Second fibrous adhesive: The first fibrous adhesive is pulverized and graded, and the D50 value is adjusted to 25 μm fibrous adhesive.

[0040] Figure 4 It is a frequency distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size (μm) and the vertical axis set to frequency (%). Figure 5 This is a cumulative distribution curve plotted for fibrous adhesives, with the horizontal axis set to particle size (μm) and the vertical axis set to cumulative volume (%). The distribution curve for the first fibrous adhesive is the curve for "Sample A". The distribution curve for the second fibrous adhesive is the curve for "Sample B". The distribution curve for the fibrous adhesive with a D50 of 116.61 μm used in Experiment 5 is the curve for "Sample 1". The distribution curve for the fibrous adhesive with a D50 of 105.37 μm used in Experiment 6 is the curve for "Sample 2". The distribution curve for the fibrous adhesive with a D50 of 82.53 μm used in Experiments 10 and 11 is the curve for "Sample 3". The distribution curve for the fibrous adhesive with a D50 of 51.5 μm used in Experiment 4 is the curve for "Sample 4".

[0041] The details of the particle size distribution measuring apparatus and the measurement conditions are shown below. The particle size distribution was measured using a wet method. The particle size of each substance in the solvent remained unchanged in the dried, formed adsorbate. The particle size distribution of each substance in the solvent reflected the particle size distribution of each substance in the dried, formed adsorbate. The results are recorded in Table 1. Laser diffraction / scattering particle size distribution measurement device: Microtrac MT3300EXII; Distribution: Volume; Solvent: Water; Measurement range: Particle size 0.021 μm to 2000 μm; Number of channels: 132.

[0042] [Table 1]

[0043] Next, the experimenter installed a ceramic core material (outer diameter φ8.1mm, inner diameter φ5.0mm) as the central core on a molding machine, and deposited it in the slurry through suction to form a molded adsorbent. The dimensions of the molded adsorbent were set as outer diameter φ24.4mm, inner diameter φ8.1mm, and length 90mm. The experimenter dried and ground the molded adsorbent, wound it with non-woven fabric, and glued a cap to it to produce a water purification filter cartridge. The density of each molded adsorbent (g / cm³) was determined. 3 The mass (g) of the formed adsorbate was measured and divided by the volume of the formed adsorbate, which was 37.4 cm³. 3 The results were calculated and recorded in Table 1.

[0044] The initial flow rate was evaluated according to JIS S3201 6.1 "Filter Flow Rate Test" as follows. Unused water filter cartridges from each test case were installed on the housing. Raw water was continuously passed through at SV = 2400 / h (1.5 L / min) for 10 minutes. While continuing to pass water, the pressure gauge was adjusted to 0.1 MPa, and the flow rate (LPM, L / min) was measured. The results are recorded in Table 1.

[0045] The chloroform removal performance was evaluated according to JIS S3201 as follows. Test water with a chloroform concentration of 60 ppb was prepared. The water purification filter cartridges for each test case were installed on the housing, and water was passed through at SV = 2400 / h (1.5 L / min). The cumulative flow rate (L) until the removal rate of filtered water relative to the raw water reached 80% was measured. The results are recorded in Table 1.

[0046] The results of the experiments are as follows. Experiments 4, 5, 6, 10, and 11 all satisfy conditions a, b, and c. In contrast, experiments 1, 2, 3, 7, 8, and 9 do not satisfy condition b. Experiments 1, 3, 7, 8, and 9 also do not satisfy condition c. Condition a: Contains activated carbon and fibrous binder. Condition b: The fibrous adhesive is a mixture of a first fibrous adhesive and a second fibrous adhesive having a different particle size distribution than the first fibrous adhesive. When the first fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 80 μm or more and 300 μm or less. When the second fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 14 μm or more and 60 μm or less. Condition c: Able to form and produce a shaped adsorbent.

[0047] Experiments 4, 5, 6, 10, and 11 showed no cracks in the formed adsorbent, demonstrating good shape retention. The chloroform removal performance of these experiments was above 1390 L, with an initial flow rate above 1.05 LPM. These experiments, while improving the shape retention of the formed adsorbent, ensured the required chloroform removal capacity and initial flow rate for a formed adsorbent.

[0048] In Experiments 4, 5, 6, 10, and 11, Experiments 4, 5, and 6 also satisfy the following condition d. Condition d: The content of activated carbon with a particle size of less than 10 μm is less than 12% by volume.

[0049] The initial flow rates in Experiments 4, 5, and 6 were above 1.50 LPM. This shows that satisfying condition d above further ensures the initial flow rate. Explanation of reference numerals in the attached figures

[0050] 1: Formed adsorbent; 3: Activated carbon; 5: Lead removal materials; 7: Fibrous adhesive; 7A: First fibrous adhesive; 7B: Second fibrous adhesive; 11: Water purifier filter cartridge; 12: SMIC; 14: Non-woven fabric; 15: Sealing cap; 16: Sealing cap; 20: Flow path; 60: Discharge outlet.

Claims

1. A shaped adsorbent comprising activated carbon and a fibrous binder, characterized in that, The fibrous adhesive is a mixture of a first fibrous adhesive and a second fibrous adhesive, wherein the second fibrous adhesive has a different particle size distribution than the first fibrous adhesive. When the first fibrous adhesive was measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 was 80 μm or more and 300 μm or less. When the second fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the measured value as the central particle size D50 is 14 μm or more and 60 μm or less.

2. The shaped adsorbent according to claim 1, characterized in that, The content of the activated carbon with a particle size of less than 10 μm is less than 12% by volume.

3. The shaped adsorbent according to claim 1 or 2, characterized in that, When the fibrous adhesive is measured using a laser diffraction / scattering particle size distribution measuring device, the content of the fibrous adhesive with a particle size of 23.99 μm or less is 11% by volume or more and 30% by volume or less.

4. A water purification filter element, characterized in that, The shaped adsorbent comprises any one of claims 1 to 3.

Citation Information

Patent Citations

  • Water processing filter and manufacturing method therefor

    WO2014061740A1